Multidrug-resistant Serratia rubidaea strains in the oral microbiota of healthy horses - José da Costa Pimenta (Tripoli University, 2021)
Background: Many emergent pathogenic agents are cross-transmitted from animals to humans. Horses are considered potential reservoirs of commensal, zoonotic and multidrug-resistant bacteria. Equine bites could lead to infections caused by these agents, considering equine species as a public health concern. The more it is known about the equine oral microbiota the best secondary problems created by their commensal flora can be controlled. There are very few reports of Serratia rubidaea, a zoonotic and opportunistic bacterium, both in human and veterinary medicine. Aim: This study aimed to evaluate the Gram-negative microbiota of healthy equine oral cavities and their antimicrobial susceptibility. Methods: During equine routine oral procedures, eight healthy horses were selected for this study, after discarding any abnormal dental conditions. Samples were collected from the subgingival space and gingival margin from the tooth 406 and both the identification and antimicrobial susceptibility test of Gram-negative bacteria were performed. Results: This study reports the isolation of 32 Gram-negative agents, 27 of which were multidrug-resistant to the antimicrobial classes tested. High resistance rates were obtained to commonly used antimicrobial drugs, particularly macrolides and aminoglycosides as to carbapenems that are specific to human medicine. Two multi-drug resistance strains of Serratia rubidaea were found in the mouth of two healthy horses. Conclusion: Most Gram-negative isolates found in healthy horses were zoonotic and multi-drug resistant. This is a strong reason to consider the horse as an animal with a major place in the “One Health” concept. Equine clinicians should take precautions when working with horses’ mouths. Antimicrobial sensitivity tests should be taken into consideration when finding the appropriate antimicrobial therapy protocol. To our best knowledge, this is the first report about isolation of Serratia rubidaea from the mouth of the equine species.